The complete mitochondrial genome of the endemic and highly specialized South African bee species Rediviva intermixta (Hymenoptera: Melittidae), with a comparison with other bee mitogenomes. (25th August 2015) - Kahnt, Belinda; Gerth, Michael; Paxton, Robert J.; Bleidorn, Christoph; Husemann, Martin
<x xml:space="preserve">Abstract</x> We describe the complete mitochondrial genome (mitogenome) of the South African bee Rediviva intermixta, the first mitogenomic data for a species belonging to the basally branching bee family (Melittidae), and compare it with other published bee (Anthophila) mitogenomes. The mitogenome of R. intermixta is 16 875 bp long, shows the highest GC content (20.1%) of all studied bee mitogenomes and contains the typical set of 37 genes. The order of protein‐coding and rRNA genes is highly conserved across Anthophila, but several tRNA rearrangements have occurred. These were mostly observed in the first and sixth (nad3–nad5 junction) tRNA clusters, which are considered rearrangement hotspots in other taxa. All protein‐coding genes contained the common start and stop codons, with cox2 and nad1 having two consecutive stop codons. The mean genetic distance between R. intermixta and the other Anthophila ranged from 29 to 33%. Phylogenetic analysis of the whole mitogenome supported R. intermixta and Colletidae as sister group to all other apid species. The discordance among gene sequences in phylogenetic signal detected allows selection of mitochondrial genes with greater information content for future phylogenetic analyses.